Language Variations in Captions of Covid-19 Information on Instagram: Analysis of Language and Gender and Their Relevance For Preparing High School Level RPP (Sociolinguistic Approach) - Adellita Dwisandi Setiaji, Wulan; Meliasanti, Ferina; Setiawan, Hendra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research discusses language and gender variations in Instagram captions. The aim of this research is to find the influence of gender on language variations in Instagram captions, describe the results of interpretation and analysis of @drningz and @adamprabata Instagram captions regarding Covid-19 information, realize the meaning based on the results of analysis using the Computer Mediated Discourse Analysis (CMDA) approach. using language in the virtual world or the internet as well as creating RPPs (Learning Implementation Plans) and expository text teaching materials for high school level students. This research uses a descriptive qualitative method with data collection techniques of non-participant observation, documentation and note-taking, in the form of screenshots containing captions with the theme of Covid-19 on Instagram social media. Data analysis in this research refers to Lakoff's (1975) theory regarding the language features used by women and men. The results of the analysis show that the variations of language on Instagram used by men and women tend to have many similarities, namely showing the characteristics of a variety of spoken languages. Expert doctors, both male and female, both realize language variations in Instagram captions by conveying goals or intentions. The differences in language used by gender are not very significant and tend to have many similarities.